Purebred dead - Delaney, Kathleen (Delaney, Kathleen. Mary McGill and Millie series., 2015)
Pillar of the community, Mary McGill has a finger in every pie, a place on every committee. She's the one the townsfolk can count on when they need help. Everything Mary organizes runs smoothly - apart, that is, from the town's traditional Christmas pageant. For the festivities are rudely interrupted by the discovery of a blood-stained corpse lying in the manger. Cowering beside the body is a small black-and-white puppy. Two local children report seeing a shadowy figure fleeing from the scene - but there are no clues as to the murderer's identity. If Mary could only find out what the puppy was doing there, she would be one step closer to finding the killer. As someone who knows nothing about dogs, purebred or otherwise, Mary had better learn - and fast - before she and the children become the next victims.